2018
DOI: 10.1186/s12903-018-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of child characteristics and dental history on dental fear: cross-sectional study

Abstract: BackgroundDental fear (DF) is a challenging problem in dentistry. It is multifactorial in origin and many contributing factors have been identified. The aim of the study was to assess dental fear among 12–15 years old Arabic speaking children in Jeddah, Saudi Arabia and its relation to demographic variables, previous dental experience, and child behaviour.MethodsIn this cross-sectional study, a total of 1522 boys and girls from middle schools in Jeddah, Saudi Arabia participated in this study during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
57
6
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 33 publications
11
57
6
13
Order By: Relevance
“…Moreover, we did not find a difference between the pain felt by boys vs girls. Contrary to our results, some studies showed significantly higher dental anxiety in girls as compared to boys …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, we did not find a difference between the pain felt by boys vs girls. Contrary to our results, some studies showed significantly higher dental anxiety in girls as compared to boys …”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our results, some studies showed significantly higher dental anxiety in girls as compared to boys. 28,29 For the secondary outcomes, we found statistically significant evidence in favour of IOA for latency, about 1.5 minutes. However, we did not assess injection time, which could be longer for IOA, because it was delivered by a computerized system at a constant rate and pressure.…”
Section: Discussionmentioning
confidence: 73%
“…[6][7][8]14,19 The fact that age was associated with dental anxiety was expected, given that maturation increases over time in children. 20,21 However, children at this age can understand the importance of the procedure they are about to undergo and can control their dental anxiety, enabling the dentist better management of the child. A previous study found that negative behaviour decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…1 Children's DFA is a dynamic process that depends on many different factors, such as age, gender, maternal dental fear, unbearable pain during the first dental visit, and even the sweet consumption frequency. 2,3 With that, the associations of DFA prevalence with age and sex are not almost clear. It is considered that younger children and girls have higher odds of displaying negative behavior, and that girls usually have higher rates of severe dental fear than boys.…”
Section: Introductionmentioning
confidence: 99%